2016
DOI: 10.1007/s10517-016-3594-9
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotoxic and Dyslipidemic Effects of Doxorubicin and Betulinic Acid Amide

Abstract: Changes in the blood lipid spectrum and structural reorganization of the rat myocardium in response to injection of a single sublethal dose of doxorubicin (7 mg/kg) alone and in combination with course administration of betulonic acid amide (100 mg/kg/day for 14 days) were studied. Betulinic acid amide in the specified dose exhibited less pronounced cardiotoxic (necrobiotic impairment of cardiomyocytes) and dyslipidemic (increase of cholesterol and triglyceride levels) effects in comparison with doxorubicin. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…On the other hand, the enhancements of plasma levels of total cholesterol and non-HDL-c in both control and F-overloaded rats, after DOX injection are consistent with the dyslipidemic effects of this compound in rodents 44–46 and humans. 47 It has been shown that chronic or subchronic treatments with DOX decreases HDL-c plasma levels, 47–49 and it is believed that this effect contributes to the deleterious action of the drug because there is evidence that HDL-c attenuates the cardiotoxic effects of DOX by protecting cardiomyocytes from apoptosis in vitro 48 and by maintaining cardiac function in vivo.…”
Section: Discussionsupporting
confidence: 71%
“…On the other hand, the enhancements of plasma levels of total cholesterol and non-HDL-c in both control and F-overloaded rats, after DOX injection are consistent with the dyslipidemic effects of this compound in rodents 44–46 and humans. 47 It has been shown that chronic or subchronic treatments with DOX decreases HDL-c plasma levels, 47–49 and it is believed that this effect contributes to the deleterious action of the drug because there is evidence that HDL-c attenuates the cardiotoxic effects of DOX by protecting cardiomyocytes from apoptosis in vitro 48 and by maintaining cardiac function in vivo.…”
Section: Discussionsupporting
confidence: 71%
“…Instead, even though evidence is limited, anthracyclines have shown to be potentially detrimental for lipid metabolism. This association was initially observed in animal studies, where doxorubicin induced a three-fold increase in LDL levels 14 days after injection [50,51]. Anthracyclines have also appeared to be independently associated with higher levels of triglycerides in a retrospective analysis conducted on 1934 patients undergoing adjuvant chemotherapy [52].…”
Section: Lipid Metabolism and Dyslipidemiamentioning
confidence: 75%
“…In the evaluation there was no statistical difference in the density of cardiac fibers, contrary to what was described in a study conducted with rats evaluating doxorubin carditoxicity. However, changes in the evaluated parameter were evident only after days of chemotherapy administration, showing a late marker for myocardial toxicity (Klinnikova et al 2016).…”
Section: Discussionmentioning
confidence: 97%